Understanding Information Technology for increasing Professionality of The State Civil Apparatus in The Regional Forestry Office of North Sulawesi Province - Setiawan, Enrico; Mamonto, Fitri H.; Wawointana, Thelma (JR Education, 2022)
Desired goal achieved by one organization Governance is heavily influenced by quality role Apparatus State Civil. Where is development will could be done in accordance destination if Source Human Resources (HR) used adequate, fine that implementation development National and Regional level. Development this Source Power Humans who are something must absolute both facing _ demands Duty or now and in times to come. Government institutions need human resources who can carry out good governance by utilizing information and communication technology in order to provide better public services. Because the higher the quality of Human Resources, the better the performance, especially in terms of public services now. With existence Settings management Source Power Man in a manner professional, then officials expect _ State Civilians can give maximum contribution as has been expected. However, based on observation beginning researcher that work professional level employee at the forestry office North Sulawesi province still less and need there is study more carry on is ASN professionalism in the Service has problem in connection with professionality work. Method study in Thing this working for answer problem. So, type study this use type study or method study qualitative. Method model study this usually used performance observation and research social. professionalism be measured from terms: Competence Employees, Effectiveness Employee, Efficiency Employees, and Employee Responsibilities. Based on results discussion that has been writer present in chapters before, then writer d concluded that Professionalism Employee Apparatus State Civil Service (ASN) at the Regional Forestry Service of North Sulawesi Province walk with Professional only just needed a number of improvements.